The regulated expression of an intrabody produces a mutant phenotype in Drosophila. - Hassanzadeh, G.G.; Devoogdt, N.; Ghysen, A.; de Baetselier, P.; Muyldermans, S.; Dambly-Chaudiere, C. (FEBS Letters, 1998)
Intrabodies show great promise for controlling gene expression. As an initial attempt to evaluate the intrabody technology in Drosophila, the gene poxn was used as target. Transgenic flies harboring different anti-Poxn scFv genes integrated into various chromosomes were obtained. In one transformant, a phenocopy resembling the hypomorphic poxn-phenotype was produced in embryos and larvae following induction of expression of alpha-Poxn2 intrabody. The antisense approach was used as control. Parameters that can affect the success of intrabody technology are described.